Accumulation, depuration and distribution of cadmium and zinc in the green-lipped mussel Perna viridis (Linnaeus) under laboratory conditions - Yap, C.K.; Ismail, A.; Tan, S.G.; Omar, H. (Kluwer Academic Publishers, 2003)
Ecotoxicological tests were conducted in the green-lipped mussel Perna viridis under laboratory conditions. Different rates of accumulation and depuration in soft tissues are found and this might be due to different mechanisms of metal binding and regulation. At the end of depuration, Cd levels in soft tissues of P. viridis were 10-30 times higher than before exposure, while Zn levels in soft tissues were almost similar to levels before exposure. These results indicate that P. viridis is a good biomonitoring organism for Cd but Zn levels might be actively regulated. It remains uncertain whether P. viridis is a good biomonitoring organism of environmental Zn contamination. However, the positive patterns, although different rates, of accumulation and depuration for Cd and Zn support the use of P. viridis as a biomonitoring agent for such metals.